The Influence Of Perceived Product Quality, Perceived Marketing Quality And Social Media Marketing On Consumer Buying Interest - Setia Pratama, Ade (International Journal of Science, Technology & Management, 2024)
This research was conducted with the aim of finding out how much influence product quality, service quality and social media marketing have on consumer buying interest at the Batik Gallery of the East Java Province Cooperative and SME Service, partially and simultaneously and how much influence they have. This research data was obtained from primary data through interviews and distributing questionnaires to consumers who had purchased products at the Batik Gallery of the East Java Province UKM Service. In this study, researchers used the Lemeshow formula to obtain the population size and obtained 96 data samples for processing. In this research the author used quantitative descriptive methods. The analysis used is multiple linear regression analysis, t test, F test, classical assumption test, and coefficient of determination test using the SPSS version 23 application. The questionnaire in this research has also passed the validity and reliability testing stage. The results of the partial test (t-test) between the product quality variable (X1) and purchasing interest (Y), can be concluded that the product quality variables (X1) and (Y) have no partial influence. The service quality and social media marketing variables have a partial influence. Meanwhile, the results of simultaneous testing (F-test) can be concluded that there is a significant simultaneous influence between the variables product quality (X1), service quality (X2) and social media marketing (X3) on consumer buying interest (Y).